Calculation Of Capilarity Constants In Ostwald Viscometer Using The Water Viscosity Approach - Fadhilah, Rahadyan Itsar; Ahmad Zaenal Arifin; Saputro, Erwan Adi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Each fluid possesses unique characteristics that distinguish it from others. One such characteristic is viscosity, with each fluid having its own viscosity coefficient. Viscosity can be considered as the internal movement within a fluid, influenced by strong intermolecular forces in the liquid. A commonly used device for determining fluid viscosity is a viscometer, which accurately and specifically measures viscosity according to predefined standards. The Ostwald viscometer is a widely used instrument, but it comes in different types, including the one-ball and two-ball Ostwald viscometers, each yielding different constants. This study aims to determine the constant coefficients of the one-ball and two-ball Ostwald viscometers, simplifying the determination of fluid viscosity through experimentation. The results indicate that the capillary constant of the first Ostwald viscometer is greater than that of the second. Specifically, the capillary constant for the first Ostwald viscometer is , while for the second Ostwald viscometer, it is .